In Vitro Synovial Membrane 3D Model Developed by Volumetric Extrusion Bioprinting - Mauro Petretta; Simona Villata; Marika Pia Scozzaro; Livia Roseti; Marta Favero; Lucia Napione; Francesca Frascella; Candido Fabrizio Pirri; Brunella Grigolo; Eleonora Olivotto (Applied Sciences, 2023)
(1) Background: Synovial tissue plays a fundamental role in inflammatory processes. Therefore, understanding the mechanisms regulating healthy and diseased synovium functions, as in rheumatic diseases, is crucial to discovering more effective therapies to minimize or prevent pathological progress. The present study aimed at developing a bioartificial synovial tissue as an in vitro model for drug screening or personalized medicine applications using 3D bioprinting technology. (2) Methods: The volumetric extrusion technique has been used to fabricate cell-laden scaffolds. Gelatin Methacryloyl (GelMA), widely applied in regenerative medicine and tissue engineering, was selected as a bioink and combined with an immortalized cell line of fibroblast-like synoviocytes (K4IM). (3) Results: Three different GelMA formulations, 7.5–10–12.5% w/v, were tested for the fabrication of the scaffold with the desired morphology and internal architecture. GelMA 10% w/v was chosen and combined with K4IM cells to fabricate scaffolds that showed high cell viability and negligible cytotoxicity for up to 14 days tested by Live & Dead and lactate dehydrogenase assays. (4) Conclusions: We successfully 3D bioprinted synoviocytes-laden scaffolds as a proof-of-concept (PoC) towards the fabrication of a 3D synovial membrane model suitable for in vitro studies. However, further research is needed to reproduce the complexity of the synovial microenvironment to better mimic the physiological condition.